A charging time energy fraction method for evaluating the performance of a latent thermal energy storage heat exchanger. (August 2021) - Beyne, Wim; Couvreur, Kenny; T' Jollyn, Ilya; Tassenoy, Robin; Lecompte, Steven; De Paepe, Michel
Highlights: The charging time energy fraction method is developed. The method allows to predict the outlet as a function of the input conditions. The method is used to develop a model for a specific heat exchanger. The predictions are mostly within the measurement uncertainty. Abstract: Latent thermal energy storage heat exchangers have a large potential in different processes. Implementing such a heat exchanger requires evaluating the performance of the heat exchanger in the conditions of each specific process. Therefore a method to characterize the performance of a latent thermal energy storage design would be a useful tool for designing processes. Characterization methods for heat exchangers such as the effectiveness number of transfer units method are based on the steady-state operation of the heat exchanger. However, latent thermal energy storage heat exchangers do not operate in steady state and therefore the standard methods are not applicable. The present paper develops a novel method to determine the heat transfer fluid outlet state as a function of the initial and input conditions: the charging time energy fraction method. This method is used to characterize and evaluate a latent thermal energy storage channel heat exchanger. For 26 out of 30 calibration and validation experiments, the model predicts the outlet heat transfer fluid temperature within measurement uncertainty (±0.15 °C) during all but the initial 100 s of the charging process. The charging time energy fraction method is according to the authors the first approach to derive a predictive, low computational cost model of the outlet temperature of a latent thermal energy storage heat exchanger from a set of experiments.